MnO2-Coated Sulfur-Filled Hollow Carbon Nanosphere-Based Cathode Materials for Enhancing Electrochemical Performance of Li-S Cells. Issue 8 (1st January 2019) - Yue, Zheng; Dunya, Hamza; Kucuk, Kamil; Aryal, Shankar; Ma, Qiang; Antonov, Stoichko; Ashuri, Maziar; Alabbad, Bader; Lin, Yiwei; Segre, Carlo U.; Mandal, Braja K.
Abstract : When comes to very high energy density energy storage systems, the prospect of lithium-sulfur battery (LSB) technology is very promising. The major problem that prevents the commercial production of LSBs is their poor cycling life caused by the migration of polysulfide intermediates from the cathode structure to the anode. Confining sulfur and the discharged polysulfide intermediates inside conductive porous carbon matrices is regarded as a promising and effective strategy to overcome this problem. In this study, a new class of MnO2 -coated sulfur-filled hollow carbon nanosphere (HCN)-based cathode materials has been prepared to improve the electrochemical performance of Li-S Cells. The cathode materials constructed with silica nanoparticle hard templates displayed a high initial capacity of 834 mAh g −1  with a capacity fading rate of 0.080% per cycle. This material also showed superior redox kinetics, which enabled the Li-S cells to run at a higher charging-discharging current density.